GESTURES AS A COMMUNICATION FEATURE IN CHILDREN WITH DEVELOPMENTAL LANGUAGE DISORDER - Tūbele, Sarmīte; Anoško, Lūcija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Gestures as non-verbal communication allow us to express our attitude, emotional state, and it functions unconsciously. The verbal communication appears in the life of a child about 2 years of age and gradually replaces the non-verbal communication. However, children with DLD (Developmental Language Disorder) at the age of 3 and more do not speak or speak using separate sounds and combinations of sounds in their speech and use gestures broadly; it helps them to communicate with others. The aim of the article is to explore what kind of gestures as non-verbal communication are used by children with DLD in order to communicate with peers and adults. Based on the scientific literature of the research, the methods used are pedagogical observations, processing, and analysis of the collected data. Main conclusions – the children with DLD use gestures as a tool for communication and interaction. These children mainly use directional gestures during a communication act.